Silver Chitosan Nanocomposites are Effective to Combat Sporotrichosis - Artunduaga Bonilla, Jhon Jhamilton; Honorato, Leandro; Guimarães, Allan J.; Miranda, Kildare; Nimrichter, Leonardo (Frontiers in Nanotechnology, 2022)
The use of silver nanoparticles (AgNPs) embedded in polymeric matrix has acquired special attention as a strategy to reduce metal toxicity without losing its antimicrobial effect. In this work, the green synthesis of AgNPs and their functionalization with chitosan (AgNPs@Chi) was performed, and their antifungal activity investigated against the foremost species responsible for causing sporotrichosis, Sporothrix brasiliensis and Sporothrix schenckii. In vitro studies revealed inhibitory concentrations ranging from 0.12 – 1 µg/mL for both nanocomposites (NCs). Silver release in suspension displayed chitosan as a potential vehicle for continuous silver discharge, with a complete release after 52 days. No synergistic effects were observed in vitro when the NCs were combined with itraconazole or amphotericin B. Treatment of S. brasiliensis with NCs caused morphological deformities, cell membrane discontinuity and an intense cytoplasmic degeneration. Remarkably, both NCs induced the growth and migration of keratinocytes and fibroblasts when compared to control conditions. In addition, functionalization of AgNPs with chitosan significantly reduced its hemolytic activity, suggesting their potential use in vivo. Finally, silver nanocomposites were used as a daily topical treatment in a murine model of subcutaneous sporotrichosis, showing the ability to reduce the Sporothrix infection and stimulate tissue repair. In combination, our results demonstrate that AgNPs@Chi can be a non-toxic and efficient alternative for sporotrichosis.